Kewenangan Absolut Peradilan Tata Usaha Negara Dalam Penyelesaian Sengketa Administrasi Pasca Berlakunya Undang-Undang Administrasi Pemerintahan - Rusnin Rusnin; Almanar Almanar; Mainita Mainita; Afifuddin Afifuddin; Syarifah Sharah Natasya (Varied Knowledge Journal, 2026)
The transformation of the administrative legal framework through the enactment of the Government Administration Law has generated new dynamics in the practice of resolving administrative disputes, particularly concerning the limits of the absolute jurisdiction of the State Administrative Court (PTUN). The urgency of this research lies in the persistent lack of clarity regarding the boundaries of PTUN’s absolute competence in handling an increasingly broad range of dispute objects, including factual actions and electronic decisions, which potentially lead to overlapping jurisdiction with other courts. This study aims to analyze the scope of PTUN’s absolute jurisdiction following the enactment of the law and its implications for legal certainty. The method employed is normative legal research using statutory and conceptual approaches. Data were analyzed through a literature review of legislation, court decisions, and doctrines of administrative law. The results indicate that the expanded interpretation of State Administrative Decisions now encompasses a wider range of administrative actions, thereby broadening the absolute jurisdiction of PTUN. However, inconsistencies in practical implementation remain, particularly in the interpretation of dispute objects and the boundary between administrative and civil domains. The implications of this study highlight the need for regulatory harmonization and the strengthening of judicial guidelines to prevent jurisdictional conflicts among courts. Furthermore, enhancing law enforcement officials’ understanding of the concept of absolute jurisdiction is essential to achieving legal certainty and justice in the resolution of administrative disputes.